2009
DOI: 10.1158/1078-0432.ccr-08-1126
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HER2/neuExpression Level on Response to the E75 Vaccine: From U.S. Military Cancer Institute Clinical Trials Group Study I-01 and I-02

Abstract: Purpose: HER2/neu, a source of immunogenic peptides, is expressed in >75% of breast cancer patients. We have conducted clinical trials with the HER2/neu E75 peptide vaccine in breast cancer patients with varying levels of HER2/neu expression. Vaccine response based on HER2/neu expression level was analyzed. Experimental Design: Patients were stratified by HER2/neu expression. Low expressors (n = 100) were defined as HER2/neu immunohistochemistry (IHC) 1 + to 2 + or fluorescence in situ hybridization < 2.0. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 39 publications
1
67
0
1
Order By: Relevance
“…Particularly, the maintenance of HER2-specific CD4 C immunity in HER2 neg -IBC patients may, in part, explain their improved clinical outcomes after vaccination with HER2 peptides aimed at activating CD8 C T-cells. 25 It is somewhat surprising that HD/BDs maintained a readily identifiable population of circulating anti-HER2 Th1 cells. Since HER2 is normally a membrane constituent in branching breast ductal cells during pregnancy and lactation, 26 it is plausible that pre-existing CD4 C T-cell responses in HD/BDs are generated as a result of HER2-epitope presentation by antigen-presenting cells (APC) within the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the maintenance of HER2-specific CD4 C immunity in HER2 neg -IBC patients may, in part, explain their improved clinical outcomes after vaccination with HER2 peptides aimed at activating CD8 C T-cells. 25 It is somewhat surprising that HD/BDs maintained a readily identifiable population of circulating anti-HER2 Th1 cells. Since HER2 is normally a membrane constituent in branching breast ductal cells during pregnancy and lactation, 26 it is plausible that pre-existing CD4 C T-cell responses in HD/BDs are generated as a result of HER2-epitope presentation by antigen-presenting cells (APC) within the breast.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide a proof of concept for the potential benefit of using a combination of immunotherapeutic strategies. Finally, Benavides et al [72] have recently demonstrated that in a subset of high expressor patients (IHC 3 ? ), who received trastuzumab before vaccination, such therapeutic combination was safe and immunologically beneficial.…”
Section: E75 Peptidementioning
confidence: 99%
“…Benavides et al [72] have studied the impact of HER2 expression level on the response to the E75 vaccine. They demonstrated that most patients responded immunologically and seemed to benefit from vaccination independently from the level of HER2 expression of their cancer.…”
Section: E75 Peptidementioning
confidence: 99%
See 2 more Smart Citations